Parafia rzymskokatolicka w świadomości młodzieży polskiej przełomu wieków. Badania socjologiczne z lat 1988–2018 - Baniak, Józef (Humaniora. Czasopismo Internetowe, 2021)
In this paper I present a widely understood attitude of gymnasium, high school and academic youth in Poland in the two last decades of the 20th century and both first decades of the 21st century towards the Roman-catholic parish as a church institition and a socio-religious community of secular Catholics. The basis for the presented issues is being made by the research outcome of various sociologists of religion undertaken in the mentioned time frame. The main issue is being made here by the general question – how did shape in this time frame the attitude of the youth towards the Roman-catholic parish? The goal of this paper is to present the declaration of the youth related to the attitude towards the home parish. The presented investigations use the method of the analysis of in situ data and a comparison of various related research.